Observations on the distribution and biology of a few bathypelagic fishes from the South-West Coast of India - Mathew, Grace; Jayasankar, P; Sivakami, S; Narayanaswami, J (Indian Journal of Fisheries, 2011)
The coastal fish production is stagnating during the last few years (James et al. 1987). The only way to increase marine fish production is to exploit the untapped resources from the deeper parts of the EEZ. FORV Sagar Sampada carried out trawling surveys to locate and estimate the abundance of the deep sea resources, especially the crustaceans and fishes along the upper continental slope off K.erala c_ during January- February 1988. The present paper deals with some of the important observations in this survey.